2022
DOI: 10.3390/plants11030315
|View full text |Cite
|
Sign up to set email alerts
|

An Eruption of LTR Retrotransposons in the Autopolyploid Genomes of Chrysanthemum nankingense (Asteraceae)

Abstract: Whole genome duplication, associated with the induction of widespread genetic changes, has played an important role in the evolution of many plant taxa. All extant angiosperm species have undergone at least one polyploidization event, forming either an auto- or allopolyploid organism. Compared with allopolyploidization, however, few studies have examined autopolyploidization, and few studies have focused on the response of genetic changes to autopolyploidy. In the present study, newly synthesized C. nankingens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Elimination of most male chromosomes and extra duplication of partial chromosomes during meiotic DNA synthesis phase were observed in intertribal crosses between Brassica species (B. rapa, B. napus) and Capsella bursa-pastoris and B. rapa  O. violaceus intergeneric cross (Chen, 2007;Liu & Li, 2007). Genetic changes as the loss of old fragments and the gain of novel fragments and some novel sequences were potential long terminal repeat (LTR) retrotransposons were reported in Chrysanthemum nankingense due to genome shock following autopolyploidization that can contribute abundant raw material in adaptive evolution (He et al, 2022). In the hybrids of synthetic Brassica, Brassica oleracea allohexaploids  O. violaceus, chromosomes of O. violaceus are preferentially eliminated, whereas Brassica genomes showed stability in the order of B > A > C (Ge et al, 2009).…”
Section: Molecular Changes In Incompatible Cross Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Elimination of most male chromosomes and extra duplication of partial chromosomes during meiotic DNA synthesis phase were observed in intertribal crosses between Brassica species (B. rapa, B. napus) and Capsella bursa-pastoris and B. rapa  O. violaceus intergeneric cross (Chen, 2007;Liu & Li, 2007). Genetic changes as the loss of old fragments and the gain of novel fragments and some novel sequences were potential long terminal repeat (LTR) retrotransposons were reported in Chrysanthemum nankingense due to genome shock following autopolyploidization that can contribute abundant raw material in adaptive evolution (He et al, 2022). In the hybrids of synthetic Brassica, Brassica oleracea allohexaploids  O. violaceus, chromosomes of O. violaceus are preferentially eliminated, whereas Brassica genomes showed stability in the order of B > A > C (Ge et al, 2009).…”
Section: Molecular Changes In Incompatible Cross Derivativesmentioning
confidence: 99%
“…By isolating the genomic regions flanking the newly transposed retrotransposon Tos17 copies, Han et al (2004) identified preferential insertion of the elements in cellular genes, thereby explaining potential impacts of the transposition on the structure and expression of the targeted genes. LTR retrotransposons such as Ty1-copia and Ty3-gypsy elements are triggered by genome shock during alloploidization leading to array of genetic changes (He et al, 2022).…”
Section: Epigenetic Reprogrammingmentioning
confidence: 99%